Efficacy of a combination of conservative and surgical methods of treatment for neovaascular glaucoma associated with diabetic retinopathy and central or branch retinal vein occlusion (Ukrainian Journal of Ophthalmology, 2024)
Background: Neovascular glaucoma (NVG) is secondary glaucoma which is often resistant to medical therapy and may potentially lead to blindness.Purpose: To assess the efficacy of a combination of conservative and surgical methods of treatment for NVG associated with proliferative diabetic retinopathy (PDR) and central or branch retinal vein occlusion (CRVO or BRVO).Material and Methods: Fifty-six patients (68 eyes) with NVG were under our observation. These included 48 patients (60 eyes) with NVG associated with PDR and 8 patients (8 eyes) with NVG associated with CRVO or BRVO. The mean patient age was 64.0 ± 10.0 years. Group 1 (22 patients, 33 eyes) received hypotensive ocular hypotensive medication, retinal laser photocoagulation and intravitreal ranibizumab. In addition to the above treatment, group 2 (34 patients, 35 eyes) received filtration surgery. Of the 68 eyes, 24 received single ranibizumab 0.5 mg injection; 26 eyes, two to four injections, and 18 eyes, five or more injections.Results: The treatment resulted in a partial reduction in iris neovascularization in 53/68 eyes, and total reduction, in 15/68 eyes. In a total sample of patients, the IOP reduced from 29.1 ± 7.9 mmHg at baseline to 20.4 ± 4.8 mmHg after treatment, and the mean number of IOP-lowering medications, from 2.1 ± 1.1 at baseline to 0.9 ± 0.9 after treatment.Conclusion: The combination treatment for NVG was found to enable an IOP reduction of 29.9% and prevent a significant reduction in visual acuity in 85% of eyes with NVG.
Keywords: secondary neovascular glaucoma; retinal laser photocoagulation; intravitreal anti-VEGF injection; ranibizumab; glaucoma surgery; intraocular pressure